2011
DOI: 10.1038/nphys2006
|View full text |Cite
|
Sign up to set email alerts
|

Electron-spin excitation coupling in an electron-doped copper oxide superconductor

Abstract: High-temperature (high-T c ) superconductivity in the copper oxides arises from electron or hole doping of their antiferromagnetic (AF) insulating parent compounds. The evolution of the AF phase with doping and its spatial coexistence with superconductivity are governed by the nature of charge and spin correlations and provide clues to the mechanism of high-T c superconductivity. Here we use a combined neutron scattering and scanning tunneling spectroscopy (STS) to study the T c evolution of electron-doped sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 39 publications
(110 reference statements)
8
40
0
Order By: Relevance
“…It is interesting that a qualitatively similar spectrum with two maxima was recently observed in Ref. 7. It is worth noting that, together with main maxima, shoulders or weaker maxima at higher frequencies can be disclosed also in earlier measurements of the frequency dependence of the susceptibility (see, e.g., Refs.…”
Section: Resultssupporting
confidence: 49%
“…It is interesting that a qualitatively similar spectrum with two maxima was recently observed in Ref. 7. It is worth noting that, together with main maxima, shoulders or weaker maxima at higher frequencies can be disclosed also in earlier measurements of the frequency dependence of the susceptibility (see, e.g., Refs.…”
Section: Resultssupporting
confidence: 49%
“…As a result, although the resonance mode is broadened in energy and dampened in intensity, a relatively large spin gap can persist in BaðFe 1Àx Ru x Þ 2 As 2 . These also explain why the resonance intensity is much stronger in strongly correlated hole doped cuprates (such as YBCO and Bi2212) than those of the moderately correlated electron doped cuprates (PLCCO and NCCO) and carrier doped iron-based superconductors [15,[27][28][29][30][31][32][33].…”
mentioning
confidence: 92%
“…For high-transition temperature (High-T c ) copper oxide superconductors derived from hole or electron-doping from their antiferromagnetic (AF) parent compounds, neutron polarization analysis have conclusively shown that the collective magnetic excitation coupled to superconductivity at the AF wave vector of the parent compounds, termed neutron spin resonance 2 , has a magnetic origin [3][4][5][6][7][8][9] . Furthermore, by carrying out neutron polarization analysis with a spin-polarized incident neutron beam along the scattering wave vector Q = k i − k f (where k i and k f are the incident and final wave vectors of the neutron, respectively),x||Q; perpendicular to Q but in the scattering plane,ŷ⊥Q; and perpendicular to Q and the scattering plane,ẑ⊥Q, one can use neutron spin flip (SF) scattering cross sections σ SF xx , σ SF yy , and σ SF zz to determine the spatial anisotropy of spin excitations 1 .…”
mentioning
confidence: 99%